Variation in species assemblages due to micro-topography and flow regime govern vegetation carbon stock in seasonal floodplain wetlands - Priyanka Sarkar; Tapati Das; Dibyendu Adhikari (Ecological Processes, 2019)
Abstract Hypothesis Variation in species assemblages due to micro-topographic features and flow regime determine vegetation carbon stock in floodplain wetlands. Material and method We tested this hypothesis in Chatla—a tropical floodplain wetland located in northeast India. Five sampling stations characterized by contrasting micro-topographic and flow parameters were selected in the wetland for study. Species composition, assemblage pattern, and vegetation carbon stock were studied in these stations during three flood phases, i.e., early, middle, and late flood phases following standard methods. Univariate and multivariate statistics were used to determine the relationship between the selected environmental parameters, plant species assemblages, and vegetation carbon stock of the wetland. Results Thirty-one species of herbs and five species of shrubs were recorded from the five stations in Chatla floodplain wetland. Flow regime characterized by water flow velocity and discharge showed substantial variations across the stations. These parameters in turn are related to variations in the micro-topographic characteristics namely depth, width, and cross-sectional area of the stations. Plant species composition and abundance differed significantly with respect to micro-topography and flow regime as revealed by the cluster diagram. The canonical correspondence analysis revealed strong association of plant species assemblages with the micro-topography and flow regime within the wetland. Multiple regression analysis revealed a significant positive relationship of the vegetation carbon stock with the water discharge. Conclusions Spatial variation in plant species diversity because of micro-topography and flow regime determines the vegetation carbon stock in floodplain wetlands. Modification of these parameters by anthropogenic activities such as mining and quarrying may potentially influence the carbon stocking potential of seasonal floodplain wetlands. Therefore, appropriate measures should be taken to maintain the integrity of the natural topographic features of such wetlands.